Peningkatan Hasil Belajar Menggunakan Model Problem Based Learning (PBL) Pada Mata Pelajaran Pendidikan Pancasila Dan Kewarganegaraan (PPKn) - Zainal Abidin (International Forum of Researchers and Lecturers, 2023)
This study applies the Problem Based Learning learning model to Civics Subjects in Class VII.5 of SMP Negeri 10 Kendari to improve the student`s learning outcomes.. This research was carried out at SMP Negeri 10 Kendari which is addressed in the odd semester of 2022/2023 for two months, namely from August – September 2022. The results of the research show that the application of the Problem Based Learning (PBL) model in Civics learning has been able to improve the problem solving skills of students in class VII.5 of SMP Negeri 10 Kendari. The percentage of achievement of learning objectives or completeness of students in the pre-cycle was only 54.83% (17 students), and in cycle I was 74.8% (21 students). In cycle II, the percentage of achievement of learning objectives or completeness of students increased to 77.8% (25 students).